Identification of ketamine and norketamine in dried bloodstains on crime-scene surfaces - Risha Jasmine Nathan; Babajide Okeleye; Rabiu Abdullahi; Waliyu Oyebode (Egyptian Journal of Forensic Sciences)
Abstract Background Toxicological analysis of dried bloodstains (DBS) provides critical information for reconstructing the sequence of events at a crime scene. Drugs have higher stability in DBS relative to liquid blood owing to the arrest of enzymatic reactions in dehydrated samples. However, literature on the identification of ketamine and its metabolites in DBS is limited and is mostly focussed on the analysis of bloodstains collected on paper cards. The present study has analysed the stability of ketamine and norketamine in DBS aged on common crime scene surfaces under various storage temperatures. Coloured linen fabric and glass slide, representing porous and non-porous surfaces, respectively, were stained with a defined volume of drug-fortified whole blood and stored at room temperature (20 °C), in the refrigerator (4 °C), and freezer (− 20 °C) for 1, 7, and 14 days. Analytes were solvent-extracted using a dichloromethane: hexane (1:3 v/v) mixture, followed by gas chromatography-mass spectrometry (GC–MS) analysis with ketamine-d4 as the internal standard. Results At least 4.3 ng/mL and 8.7 ng/mL ketamine and norketamine, respectively, were detected in dried stains prepared from 5 to 50 µL whole blood corresponding to a concentration range of 10–100 ng/mL. The GC–MS method was linear in this range with a coefficient of determination, R 2 > 0.99. Recovery of the analytes was comparable (~ 100–120%) between DBS porous and whole blood, whereas it was considerably lower (~ 50%) in DBS non-porous samples due to the incomplete transfer of the stains from the glass into the extraction solvent mixture. Analyte response in DBS showed a strong correlation with that in whole blood at four concentration levels (0.1–5 µg/mL). Mean precision values (% CV) for biological and technical replicates (n = 5) were 15.0 and 6.5, respectively, and within an acceptable range. Conclusions The developed method for the analysis of ketamine and norketamine in DBS is comparable to that in other biological matrices such as whole blood under short-term storage conditions. Lower temperatures are favourable for maintaining the integrity of the samples; however, the bloodstains must be completely dried before storing them in the refrigerator or freezer for short-term (1–7 days) to prevent hydrolytic degradation of drugs. Graphical Abstract